Combined analysis of preoperative and postoperative lymphocyte-C-reactive protein ratio precisely predicts outcomes of patients with gastric cancer - Kozo Miyatani; Shohei Sawata; Masahiro Makinoya; Wataru Miyauchi; Shota Shimizu; Yuji Shishido; Tomoyuki Matsunaga; Manabu Yamamoto; Naruo Tokuyasu; Shuichi Takano; Teruhisa Sakamoto; Toshimichi Hasegawa; et al. (BMC Cancer, 2022)
Abstract Background The systemic inflammatory response resulting from the complex interactions between cancer and the host plays an important role in cancer development. Recently, the lymphocyte-C-reactive protein ratio (LCR), which is a hematological and biochemical marker that reflects the systemic inflammatory response and nutritional status, has been reported to be associated with poor survival. Similar results were observed in patients with certain cancer types. However, these studies focused on the preoperative LCR, and thus far, no studies have reported the relationship between postoperative LCR and prognosis in patients with gastric cancer (GC). Methods This study enrolled 455 patients with a histopathological diagnosis of gastric adenocarcinoma who underwent curative surgery at our institution between 2005 and 2018. The relationship between both the preoperative and postoperative LCR and the prognosis of patients with GC was retrospectively investigated. Results Preoperative LCR showed significant correlations with tumor-related factors, such as tumor size, depth of invasion, and lymph node metastasis. By contrast, no correlation was observed between postoperative LCR and tumor-related factors. The 5 year survival rate was significantly worse in patients with low preoperative LCR than in those with high preoperative LCR (65.4% vs. 83.9%, p < 0.0001). Similarly, the 5 year survival rate was also significantly worse in patients with low postoperative LCR than in those with high postoperative LCR (67.0% vs. 84.1%, p < 0.0001). Furthermore, combination analysis of the pre- and postoperative LCR revealed that the prognosis of patients with both low pre- and postoperative LCR was worse in patients with GC (5 year survival rate was 52.0%). A multivariate analysis indicated that a low pre- and postoperative LCR and age and lymph node metastasis were independent prognostic indicators. Conclusions The combination of preoperative and postoperative LCR appears to be useful in predicting the prognosis of patients with GC.